Alendronate enhances antibiotic-impregnated bone grafts in the treatment of osteomyelitis - Ozturk, Akif Muhtar (Springer-Verlag, 2007)
Bisphosphonates are systemic drugs. There is limited knowledge about their effects when applied locally and in osteomyelitis treatment. A prospective longitudinal randomised controlled study was designed in rat tibia to test the efficacy of local or systemically administered bisphosphonates for controlling the osteolytic reactions and possible effects on local infection control. Tibial osteomyelitis was induced in 72 Wistar albino rats with Staphylococcus aureus ATCC 25923 strain. Débridement was performed on all rats in all groups. No other treatment was given to the control group. Treatment groups received “plain bone grafts”, “vancomycin-loaded bone grafts”, “vancomycin-loaded bone grafts+systemic alendronate”, “alendronate-impregnated bone grafts” and “vancomycin+alendronate-impregnated grafts”. Study results were evaluated by swab cultures, radiology, quantitative computed tomography, dual-energy X-ray absorptiometry (DEXA) and histopathology. S. aureus was eradicated in groups II and IV by the sixth week. Diaphyseal widening, bone deformation, diaphyseal widening and osteolysis scores were significantly lower (p < 0.05), and bone mineral content, density measurements and DEXA scores were significantly higher (p = 0.001) with alendronate administration. Histology revealed marked osteoblastic activity. Local alendronate interfered with local infection control. Even though local alendronate at the given dose has stronger effects, the possible effects on the local inflammatory process needs to be clarified.